An Analysis of Energy Consumption in the Campus Building’s Operation (Case Study: The Building of Faculty of Engineering and Department of Civil and Environmental Engineering, Universitas Gadjah Mada) - Syarifudin Syarifudin; Ashar Saputra; Suprapto Siswosukarto (Journal of the Civil Engineering Forum, 2018)
Energy Consumption Intensity (IKE) is an indicator that is used to determine the amount of energy used per area by an air-conditioned building within a month or a year as a reference to determine how much energy conservation can be done in the building. To determine the energy consumption of buildings and to determine the savings opportunities, there should be an effort to review the energy consumption through energy audits. In this research, energy consumption analysis was conducted at the Main Office building of the Faculty of Engineering (KPFT) and Department of Civil Engineering and Environmental (CEED) of UniversitasGadjah Mada Yogyakarta. The analysis was conducted on the main variables of energy efficiency, namely: measurement of temperature and relative humidity, calculation of Overall Thermal Transfer Value (OTTV) and Roof Thermal Transfer Value (RTTV), calculation of Energy Consumption Intensity (IKE) in air-conditioned and non-air-conditioned rooms as well as an analysis of opportunities to increase the efficiency of energy consumption in the buildings.The results showed that the temperature and the relative humidity of the KPFT building = 28.4℃ and 62%, while CEED Building = 28.4℃ dan 65%. Calculation of average OTTV of the KPFT building = 17.61 W/m2 and CEED building = 43.05 W/m2. Average IKE of the KPFT building in 2015 was 3.25 kWh/m2/month and in 2016 was 3.45 kWh/m2/month, while the average IKE of CEED building in 2015 was 1.5 kWh/m2/month and in 2016 was 0.79 kWh/m2/month. Based on the calculation of IKE in both buildings, they are still considered in the category of efficient. However, based on the measurement of temperature and relative humidity, it shows that in both buildings air conditioning is still necessary to achieve the level of thermal comfort, therefore an increase of efficiency in the load is needed to avoid wastage.